PageMaker 4 for the Macintosh made easy - Matthews, Martin S. (Berkeley, California : Osborne McGraw-Hill, 1990)
Covers all the features of this newly released desktop publishing software. With hands-on exercises, Matthews guides Macintosh users through Pagemaker 4's commands, menus, and new features for creating publications such as newsletters, flyers, catalogs, brochures, and financial reports. Annotation copyright Book News, Inc. Portland, Or. Offering an insight into using Pagemaker 4 for the PC, this book is adapted for the Apple Macintosh version. The authors cover such subjects as creating a brochure, preparing a newsletter, building a catalogue and creating an annual report.
Part One: The PageMaker Environment - Desktop Publishing and PageMaker. Using the Macintosh and its Mouse. Getting Started with a Flyer. Part Two - Basic PageMaker Publications: Making a Sales Order Form. Creating a Brochure. Generating an Annual Report. Part Three - Advanced PageMaker Publications: Preparing a Newsletter. Building a Catalogue.
Includes index.
Keywords: ALDUS PAGEMAKER